Central bank macroeconomic forecasting during the global financial crisis: the European Central Bank and Federal Reserve Bank of New York experiences - Lucia Alessi; Eric Ghysels; Luca Onorante; Richard Peach; Simon Potter (European Central Bank (ECB), 2014)
This paper documents macroeconomic forecasting during the global financial crisis by two key central banks: the European Central Bank and the Federal Reserve Bank of New York. The paper is the result of a collaborative effort between staff at the two institutions, allowing us to study the time-stamped forecasts as they were made throughout the crisis. The analysis does not exclusively focuses on point forecast performance. It also examines methodological contributions, including how financial market data could have been incorporated into the forecasting process.
Keywords: C53; E37; 330; forecast evaluation; mixed frequency data sampling